Management of radix entomolaris on permanent mandibular first molar complicated with ledge: a case report - Mohamed Khazin, Sobrina; Mustaffa, Musliana (IIUM Press, 2022)
Radix entomolaris is a supernumerary root located distolingually on permanent mandibular molars. It is considered as an anatomical variant and usually curved buccolingually. The presence of radix entomolaris can be endodontically challenging to treat and susceptible to endodontic mishaps such as ledge. This report describes the management of ledge in a radix entomolaris with type-3 curvature on tooth 46. Ledge was bypassed using pre-curved K-files #10, #15, and #20 sequentially and preparation was continued using step-back technique. Then, the root canal was obturated using gutta percha and root canal sealer. Diagnostic and clinical challenges in managing radix entomolaris, and prevention and management of ledge were also discussed.